Evaluating the Basa-Samawa Platform through WebQual 4.0 and Importance–Performance Analysis - Shinta Esabella; Tri Susilawati; Titi Andriani; Muhammad Hidayatullah; Gunawan Gunawan; Yana Karisma (Universitas Bumigora, 2026)
The rapid technological development in the era of Industry 4.0 has significantly influenced the education sector, including the implementation of digital learning methods such as e-learning. This research aims to develop and evaluate a responsive web-based e-learning application for learning the Samawa (Sumbawa) regional language, in response to the declining interest of younger generations in regional languages and the increasing threat of language extinction. The methodology is a quantitative descriptive approach using WebQual 4.0 and Importance-Performance Analysis (IPA) to measure user perceptions and satisfaction with the e-learning system. Data were collected through questionnaires distributed to 170 respondents, including 25 teachers and 145 students in Sumbawa Regency, using simple random sampling. The questionnaire covered three key variables: usability, information quality, and interaction quality. The results of the validity and reliability tests confirmed that the instrument was appropriate for data collection. Descriptive statistics indicated that users generally rated the e-learning application positively, although there were discrepancies between perceived performance and expectations, particularly regarding usability and interaction.IPA quadrant analysis revealed that several indicators, especially related to navigation and content accuracy, fall into the ”main priority” category and require immediate improvement. Overall, the average performance score (3.76) was slightly below the expected average (3.84), indicating the need for further refinement in certain features. The integration of WebQual 4.0 and IPA effectively identified user needs and can serve as a framework for the continuous improvement of regional language e-learning systems.